Influence of Socio-Cultural Factors on Consumer Buying Behavior in Chain Supermarkets in Kenya - Kiboro, Grace; Omwenga, Jane; Iravo, Mike (Journal of Marketing Studies, 2022)
Purpose: The objective of the study was to establish the effect of socio-cultural factors on consumer buying behavior in in supermarkets in Kenya. Methodology: The target population consisted of 33 chain supermarkets in Kenya. The target population comprised of 634 employees from these supermarkets. Descriptive research design was used for this study. In addition, regression and correlation analysis was used to link the relationships between the dependent and the independent variables. Results: The study found out that there was a positive and significant relationship between socio-cultural factors and consumer buying behavior (r=0.73, p=0.000). Unique Contribution to Theory and Practice: The study concluded that socio-cultural factors has a positive and significant effect on Consumer Buying Behavior. The study recommends for chain supermarkets to consider social cultural factors in their marketing programs since they are very crucial. This will enable them to produce goods and services that attract their target consumers and enhance business performance. Keywords: Socio-cultural factors, consumer buying behavior and supermarkets.